ChemInform Abstract: Application of Pyranoside Phosphite‐Pyridine Ligands to Enantioselective Metal‐Catalyzed Allylic Substitutions and Conjugate 1, 4‐Additions. Issue 7 (18th February 2014) - Lega, Mattteo; Margalef, Jessica; Ruffo, Francesco; Pamies, Oscar; Dieguez, Montserrat
Abstract A range of phosphite‐pyridine ligands is applied in various Pd‐catalyzed allylic substitution reactions as well as 1, 4‐addition reactions with dialkylzincs.